2020
DOI: 10.1021/acsami.0c00025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrocatalytic HER Studies of Carbene-Ligated Cu3–xP Nanocrystals

Abstract: N-heterocyclic carbenes (NHCs) are an important class of ligands capable of making strong carbon-metal bonds. Recently, there has been a growing interest in the study of carbene-ligated nanocrystals, primarily coinage metal nanocrystals, which have found applications as catalysts for numerous reactions. The general ability of NHC ligands to positively affect the catalytic properties of other types of nanocrystal catalysts remains unknown. Herein, we present the first carbenestabilized Cu3-xP nanocrystals. Inqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…As a second example, Tappan et al recently made use of an NHC ligand to greatly improve the HER catalysis of Cu 3−x P NCs, where the strong electron donation from the ligand reduced the electrostatic repulsion between Cu + and H + . 304 In another study, the HER activity of Ru NCs was demonstrated to increase in the presence of phenylpyridine ligands, in both acidic and basic media. 305 This result was attributed to the moderate metal−ligand binding strength, which permitted a larger number of H atoms to adsorb to the surface.…”
Section: Nanocrystal-based Compositesmentioning
confidence: 97%
See 1 more Smart Citation
“…As a second example, Tappan et al recently made use of an NHC ligand to greatly improve the HER catalysis of Cu 3−x P NCs, where the strong electron donation from the ligand reduced the electrostatic repulsion between Cu + and H + . 304 In another study, the HER activity of Ru NCs was demonstrated to increase in the presence of phenylpyridine ligands, in both acidic and basic media. 305 This result was attributed to the moderate metal−ligand binding strength, which permitted a larger number of H atoms to adsorb to the surface.…”
Section: Nanocrystal-based Compositesmentioning
confidence: 97%
“…Specifically, the most electron-donating ligand induced the lowest overpotentials, smallest Tafel slopes, and charge-transfer resistances; the overpotential was regulated by 0.5 V just by tuning the ligands, thus demonstrating the huge potential of such approaches. As a second example, Tappan et al recently made use of an NHC ligand to greatly improve the HER catalysis of Cu 3–x P NCs, where the strong electron donation from the ligand reduced the electrostatic repulsion between Cu + and H + . In another study, the HER activity of Ru NCs was demonstrated to increase in the presence of phenylpyridine ligands, in both acidic and basic media .…”
Section: Nanocrystal-based Compositesmentioning
confidence: 99%
“…However, as a p-type semiconductor material, its electrical and optical properties and applications have been neglected. [12][13][14][15][16][17][18][19] Mu et al synthesized self-doped colloidal copper phosphide (Cu 3ÀX P) nanocrystals in solution using a "one-pot method" and found that Cu 3ÀX P emitted uorescence at 550-650 nm. 20 The above reports indicate that Cu 3ÀX P is a kind of uorescent material, which has potential uses in uorescence emission and photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively little work has been done on non-metal NHC-stabilized nanocrystals (e.g., binary metal chalcogenide or phosphides). We were the first to report the synthesis of NHC-stabilized coinage metal chalcogenide (i.e., Ag 2 S, Ag 2 Se, Cu 2– x S, CuS, Cu 2– x Se, and CuSe) and phosphide (i.e., Cu 3– x P) nanocrystals starting from NHC-MBr (M = Ag or Cu) precursors in the absence of any additional supporting ligands. ,, We observed large differences in the colloidal stability of NHC-Ag nanocrystals (∼1 week) versus NHC-Ag 2 S nanocrystals (>6 months) . Density functional theory (DFT) calculations revealed significantly higher binding affinities between the NHC and the Ag 2 S nanocrystal surface over the Ag nanocrystal surface, with NHC binding energies ( E b ) of 0.57–0.70 and <0.30 eV, respectively.…”
Section: Introductionmentioning
confidence: 89%